Effects of different pressure midfoot wraps on balance and proprioception in amateur basketball athletes - Wu, Chengliang; Zhang, Shuai; Wu, Tao; Jia, Sheng-Wei; Chu, Zhaowei; Yang, Fan (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAnkle sprains are prevalent in basketball. This study sought to determine how midfoot wraps affect postural stability and ankle proprioception.MethodsTwenty-two amateur basketball athletes performed three single-leg balance tests (static, head-elevated static, and unstable foam pad) under four wrap conditions (no wrap, low, medium, and high pressure), and balance measures were taken using a force platform. Standing time, center of pressure dynamics, surface electromyographic of the supporting leg musculature were recorded. Ankle proprioception joint position matching error was assessed by a digital inclinometer.Results and discussionResults indicated that during balance tests on foam padding, participants demonstrated significantly longer standing time when wearing low-pressure midfoot wraps, compared to high-pressure wraps (F (3,63) = 4.32, p = 0.008, η2 = 0.17). Wearing high-pressure wraps reduced anterior-posterior dynamic stability index variability (F (3,63) = 3.89, p = 0.044, η2 = 0.16), suggesting enhanced sagittal-plane control. Intriguingly, high-pressure conditions evidenced convergent activation trends between medial and lateral gastrocnemius (GM/GL ratio shift from 1.3 to 1.0), albeit without statistical significance (p > 0.05). No significant difference was detected in joint position sense in ankle dorsiflexion, plantarflexion, eversion and inversion between different wrap conditions (p > 0.05). These findings suggest that low-pressure midfoot wraps may improve balance through enhanced cutaneous feedback, while high-pressure wraps enhance anterior-posterior dynamic stability, providing biomechanically informed strategies for ankle injury prevention in basketball.